2020
DOI: 10.1007/s13280-020-01333-9
|View full text |Cite
|
Sign up to set email alerts
|

Why bees are critical for achieving sustainable development

Abstract: Reductions in global bee populations are threatening the pollination benefits to both the planet and people. Whilst the contribution of bee pollination in promoting sustainable development goals through food security and biodiversity is widely acknowledged, a range of other benefits provided by bees has yet to be fully recognised. We explore the contributions of bees towards achieving the United Nation's Sustainable Development Goals (SDGs). Our insights suggest that bees potentially contribute towards 15 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
105
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(110 citation statements)
references
References 87 publications
1
105
0
4
Order By: Relevance
“…Adult honeybees harbour a specialized gut microbiota of relatively low complexity with diet as a major factor influencing differences in bacterial loads [ 4 ]. Although honeybee microbiome core species composition is quite consistent regardless of environmental, geographical and genetic differences between specimens [ 2 ], some studies indicate that it can be sensitive to infection, changes in diet, malnutrition and many anthropogenic activities, such as extensive pesticide use and urban land-use changes [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adult honeybees harbour a specialized gut microbiota of relatively low complexity with diet as a major factor influencing differences in bacterial loads [ 4 ]. Although honeybee microbiome core species composition is quite consistent regardless of environmental, geographical and genetic differences between specimens [ 2 ], some studies indicate that it can be sensitive to infection, changes in diet, malnutrition and many anthropogenic activities, such as extensive pesticide use and urban land-use changes [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Honey bees are important pollinators with high economic value and importance considering the ecosystem [1][2][3] . Their economic significance is based on their role in crop pollination and the different bee products they make 2,3 . Honey, their most well-known product, is an important component of human nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Adult honeybees harbor a specialized gut microbiota of relatively low complexity with diet as a major factor to differences in bacterial loads [4]. Although honeybee microbiome core species is quite consistent regardless of environmental, geographical and genetic differences between specimens [2], some studies indicated that it can be sensitive to infections, changes in diet, malnutrition and many anthropogenic activities, as extensive pesticide use and urban land-use changes [5][6][7].…”
Section: Introductionmentioning
confidence: 99%